Race, gender, sexuality, and social class dimensions of inequality and identity - Ferguson, Susan J. (SAGE, 2016)
In this fully edited and streamlined Second Edition, Susan Ferguson has carefully selected readings that open readers' eyes to the ways that social statuses shape our experiences and impact our life chances. The anthology represents many of the leading voices in the field and reflects the many approaches used by scholars and researchers to understand this important and evolving subject. The anthology is organized around broad topics (Identity, Power and Privilege, Social Institutions, etc.), rather than categories of difference (Race, Gender, Class, Sexuality) to underscore this fundamental insight: race, class, gender, and sexuality do not exist in isolation; they often intersect with one another to produce social inequalities and form the bases of our identities in society.